Indicators in the context of ESG (Environmental, Social and Governance): a bibliometric study (Research, Society and Development, 2022)
Currently, the ESG concept has been adopted by several organizations as a way of translating to investors not only their financial performance, as in the past, but also reporting performance: environmental, social and governance. Thus, the importance of developing and implementing ESG indicators is recognized, especially when applied in an integrated manner. The study, therefore, aims to analyze the panorama of international scientific publications. For this, the Scopus database was used to analyze publications related to the subject between 2006-2021, in the form of a bibliometric research, showing how studies on the subject have been approached and developed. In this study, there was a growing interest in the topic based on the distribution of publications carried out over time; the incipient number of authors with more than one publication; the predominance of European institutions; the performance of a research institution related to the financial market; the growth potential for social and governance approaches; the absence of highlights among development agencies that published the most, but also the growth of these agencies in the United States, which may indicate new times on the way and, finally, identify the most active journal. This work provides guided references for those interested in learning more about what has already been established in relation to performance indicators and ESG, also listing some mapped opportunities/gaps that may enable new approaches and/or new research projects.